(untitled) (Journal of the College of Basic Education, 2022)
The study was conducted to evaluate the efficacy of Lufenuron (Match 50 Ec) with concentrations 8000, 10000 and 12000 pm in mortality of workers and soldiers’ termite M. diversus for one year and its effect on attraction and repellent of termite individuals. Results of the study showed that insect growth regulator in all concentrations in the events affected mortality of termite workers and soldiers during the early stages of treatment and that the mortality percentage vary depending on the concentration and duration of exposure. The mortality percentage were low at the beginning of treatment and gradually increased that reached 100% after 35 days from the beginning of treatment at concentrations 10000 and 12000 ppm. To increase the duration of exposure leads to low efficiency of Lufenuron in all concentrations and percentage mortality of workers has reached to 9.96, 18.08, 32.84% and for soldiers 9.96, 18.08, 33.58% at concentration 8000, 1000 and 12000 ppm respectively. The persistence time of Lufenuron effective in occurring mortality depend on concentration and reached to 35, 150 and 180 days at concentration 8000, 10000 and 12000 ppm respectively. The study results showed that termite individuals showed avoid and move away from the treated media which causing in achieving 100% mortality after 70 days from beginning of treatment at concentration 8000 and 10000 ppm and after 84 days at concentration 12000 ppm. The sensitivity of the soldiers and workers be identical from concentration of Lufenuron.